THE ILLOCUTIONARY ACTS APPEARED IN BABYMONSTER'S SONG ENTITLED “STUCK IN THE MIDDLE” - Sari, Wati Purnama (Asosiasi Dosen Muda Indonesia, 2024)
The research purpose is to identify the illocutionary acts appeared in BabyMonster’s song entitled “Stuck In The Middle”. This research used a descriptive qualitative method. Moreover, Searle (1979) theory about illocutionary acts is applied to analyze the data. The results revealed that there are 42 data found namely Assertive with 26 data, Commissive with 4 data, Directive with 3 data, and Expressive with 9 data. Through the results, it clearly stated that the most used illocutionary acts in the BabyMonster’s song entitled “Stuck In The Middle” is Assertive with 26 data. The result inferred that Assertive, the illocutionary acts used most in the song, expressed that the speaker informed about the speaker’s experiences. Those proposed something that the speaker truly believes in.